International Confederation for Cleft Lip and Palate and Related Craniofacial Anomalies Task Force Report: Beyond Eurocleft. (November 2014) - Semb, Gunvor; ,
The assigned objective for the Task Force Beyond Eurocleft was "to make recommendations for initiations of local and/or participation in multi-national cleft outcome studies and consist of individuals from the European experience with cleft outcome studies (Scandcleft, Eurocleft) and those who have initiated, or intend to initiate, similar studies in other geographical areas." By May 2013 the Task Force (TF) consisted of 183 members from 59 countries. It was agreed that this initiative should be truly global and include all cleft specialties as well as representatives from cleft support groups in recognition of the huge commitment for improving cleft care worldwide. The vision for this group is to build a dynamic, well-functioning TF that will work globally and be multidisciplinary with inclusive and respectful behavior to improve care for all individuals born with cleft lip and/or palate. As there is a large diversity in needs and interest in the group a range of parallel approaches would be required depending on the experience, resources, and challenges of regions, teams, and individuals. Important ideas for future work were: (1) Work on a global survey of access, existing outcome studies, current collaborations, and lessons learned. (2) Work towards the creation of a lasting, living resource for newcomers to intercenter collaboration that is kept fresh with new reports, copies of relevant publications, model grant applications, and a list of volunteers with the right experience to provide support and guidance for new initiatives. (3) Develop simple online training modules to provide information about the benefits and principles of multidisciplinary care, collaborative data collection and auditing short and longer-term outcomes. (4) Establish subgroups that will work within all regions of the world with regional and national leaders identified. An evaluation of current standards of care should be undertaken and country/region specific remedies to optimize treatment outcome suggested. (5) Reach agreement on minimum standards of care, minimum record collection, and reach consensus on simple outcome measures in all disciplines. This should include all cleft types and all ages. These standards could be used to encourage governments to fund multidisciplinary care. (6) Teams will be encouraged to start and continue recordkeeping using simple and agreed protocols, according to agreed standards of minimum records and later share their data with other teams and then, embark on outcome studies. (7) Teams already active in research should: Create a register for cleft professionals and teams to reach agreement of contemporary and comprehensive multidisciplinary outcome measures, explore the possibilities using modern technology and plan large multi-national studies. A patient/parent centered data collection should always be included. These studies need funding. One task could also be exploring whether health care at a distance could be initiated using new technology.